THE EFFECTS OF SPIRITUAL COUNSELING ON THE ANXIETY LEVEL OF PATIENT’S FAMILY AT THE INTENSIVE CARE UNIT (ICU) OF DR. DRADJAT PRAWIRANEGARA HOSPITAL IN SERANG, BANTEN PROVINCE, INDONESIA - Lukmanulhakim Lukmanulhakim; Delly Arfa Syukrowardi (Belitung Raya Foundation, Indonesia, 2018)
Background: Critical nursing is a specific service in giving a holistic nursing service to fulfill human response to a life-threatening problem. A critical nurse can give a social support to patient’s family through assessment, counseling, and supporting group. Counseling is combination between high technology physical caring and emotional caring, which is needed by patients and the family. Spiritual counseling is a complementary medication preferred by the family of patient who is in acute and critical care. Objective: The study aimed to identify the effects of spiritual counseling on the anxiety level of patient’s family at the ICU of dr. Dradjat Prawiranegara Hospital in Serang, Banten Province, Indonesia. Methods: The study was a pre-experimental research with one group pre-test and post-test design. The samples were 25 respondents selected using consecutive sampling technique during one month (May to June 2016). The data of anxiety level were collected using HAR-S (Hamilton Rating Scale for Anxiety) questionnaire. The data were analyzed using parametrical t-test paired sample for the variable of anxiety before and after giving spiritual counseling. Meanwhile, the variable of respondents’ characteristics to anxiety was analyzed by using independent sample test. Results: The study found that the mean of respondents’ anxiety level before spiritual counseling was 33.44 and the standard deviation was 5.213. Meanwhile, after conducting spiritual counseling, the mean was 18.60 and the standard deviation was 2.582. Bivariate analysis result showed a significant difference between anxiety level of patient’s family in ICU (Intensive Care Unit) before and after conducting spiritual counseling in which p value was 0.000, with the mean value of 14.840 and SD of 5.437. Conclusion: Nurses should be more capable in implementing the intervention of spiritual counseling to patient’s family. Spiritual counseling can give a positive alteration to the family emotional situation. It impacts on the decrease of patient’s family anxiety level. By the decrease of family anxiety level, the possibility of doing mistake in decision-making is expected to be avoided.